Boots, bikes, and bombers : adventures of Alaska conservationist Ginny Hill Wood - Wood, Ginny (Oral biography series ;, 2012)
Boots, Bikes, and Bombers presents an intimate oral history of Ginny Hill Wood, a pioneering Alaska conservationist and outdoorswoman. Born in Washington in 1917, Wood served as a Women's Airforce Service Pilot in World War II, and flew a military surplus airplane to Alaska in 1946. Settling in Fairbanks, she went on to co-found Camp Denali, Alaska's first wilderness ecotourism lodge; helped start the Alaska Conservation Society, the state's first environmental organization; and applied her love of the outdoors to her work as a backcountry guide and an advocate for trail construction a.